Odpowiedzi

2009-12-07T22:23:55+01:00
B) /*3 -> y=3x-6
c) 3x-3y=2x
3x-2x=3y /:3
1/3x=y
d) /*(4/3) -> y = 8/9x
e) 2y=1-4x /:2
y=1/2- 2x
f) 6x-2=2/3y /*(3/2)
9x-3=y
1 5 1
2009-12-07T22:27:20+01:00
B) 1\3y=x-2 | *3
y=3x-6

c) 3(x-y)= 2x
3x-3y= 2x
-3y=-x |:(-3)
y=1/3x

d)2\3x = 3\4y |*12
8x =9y |:9
8/9x =y
e) 4x+2y=1
2y=1-4x |:2
y=1/2 - 2x

f) 6x- 2\3y=2
-2/3y=2 - 6x | *(-1)
2/3y= 6x -2 |*3
2y = 18x - 6 |:2
y= 9x-3
3 2 3
2009-12-07T22:31:57+01:00
B)1\3y=x-2 /*3
y=3x-6


c) 3(x-y)= 2x
3x-3y=2x
-3y=-x /:-3
y=⅓x

d)2\3x = 3\4y /*4/3
8/9x=y

e) 4x+2y=1
2y=1-4x /:2
y=½-2x


f) 6x- 2\3y=2
-⅔y=2-6x /*3
-2y=6-18x /:-2
y=-3+9x
3 4 3